Trends in qualitative research in the Fashion universe (Revista de Ensino em Artes, Moda e Design, 2025)
This article discusses the relevance of qualitative methods in Fashion research, highlighting their selection for the capacity to provide an in-depth understanding of the dynamics, perceptions, and meanings that permeate this field of knowledge. To this end, a survey of the methodologies adopted—considering their nature, approaches, and objectives—was conducted in a Master's Program in the field. Initially, it presents an overview of qualitative research and its main approaches, such as narrative, phenomenology, grounded theory, ethnography, and case study, demonstrating their applications in investigations within the context of Fashion. Although the paper's focus is on qualitative research, the methodology adopted for this study is quantitative-exploratory in nature. The results indicate that the qualitative approach has been prominent among the analyzed master's theses, contributing significantly to both basic and applied studies while expanding the scope of research possibilities.
Keywords: fashion; methodology; qualitative approach